Cloud Computing as a Catalyst in STEM Education - Kumar, Vikas; Sharma, Deepika (International journal of information and communication technology education, 2017)
The under representation of students in STEM disciplines creates big worries for the coming demands of STEM occupations. This requires new strategies to make curriculum interesting to enhance student's engagement in learning. Technology integration in curriculum makes more interesting and engaging, where students can learn with flexibility in time and place. This methodology creates and deepens interest in students towards learning with creativity and innovation. STEM students can work on authentic and real solutions within a technology-mediated learning environment, while inculcating higher order thinking skills. Technology-mediated environments support new ideas, real time collaboration and promotes peer learning. However, affordance as an adoption factor of technology in academics can be addressed by cloud computing technology. STEM education on cloud computing technology will gain access to its content rich features based on flexibility, accessibility, scalability, affordability, and reliability and enhanced agility. The cloud computing based STEM education infrastructure will inculcate development and experimentation skills in students. The present work (a) reviews scholarly work in cloud computing technology for simulations and prototypes for different STEM subjects, (b) outlines the benefits of using cloud computing technology for students pursuing STEM careers, and (c) presents the case studies of the successful implementation of cloud computing in STEM disciplines.